DNA methylation profiling identifies two distinct subgroups in breast cancers with low hormone receptor expression, mainly associated with HER2 amplification status - Jurmeister, Philipp; Weber, Karsten; Villegas, Sonia; Karn, Thomas; Untch, Michael; Thieme, Anne; Müller, Volkmar; Taube, Eliane; Fasching, Peter; Schmitt, Wolfgang D.; Marmé, Frederik; Stickeler, Elmar; et al. (Clinical epigenetics, 2021)
Current clinical guidelines suggest that breast cancers with low hormone receptor expression (LowHR) in 1-10% of tumor cells should be regarded as hormone receptor positive. However, clinical data show that these patients have worse outcome compared to patients with hormone receptor expression above 10%. We performed DNA methylation profiling on 23 LowHR breast cancer specimens, including 13 samples with HER2 amplification and compared our results with a reference breast cancer cohort from The Cancer Genome Atlas to clarify the status for this infrequent but important patient subgroup.